A novel locus from the wild allotetraploid rice species Oryza latifolia Desv. confers bacterial blight (Xanthomonas oryzae pv. oryzae) resistance in rice (O. sativa) - Angeles-Shim, Rosalyn B.; Shim, Junghyun; Vinarao, Ricky B.; Lapis, Ruby S.; Singleton, Joshua J. (Public Library of Science, 2020)
Bacterial blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is a major limiting factor to rice productivity worldwide. Genetic control through the identification of novel sources of bacterial blight resistance and their utilization in resistance breeding remains the most effective and economical strategy to manage the disease. Here we report the identification of a novel locus from the wild Oryza species, Oryza latifolia, conferring a race-specific resistance to Philippine Xoo race 9A (PXO339). The locus was identified from two introgression lines i.e. WH12-2252 and WH12-2256 that segregated from O. latifolia monosomic alien addition lines (MAALs). The discrete segregation ratio of susceptible and resistant phenotypes in the F2 (χ2[3:1] = 0.22 at p>0.05) and F3 (χ2[3:1] = 0.36 at p>0.05) populations indicates that PXO339 resistance in the MAAL-derived introgression lines (MDILs) is controlled by a single, recessive gene. Genotyping of a total of 216 F2, 1130 F3 and 288 F4 plants derived from crossing either of the MDILs with the recurrent parent used to generate the MAALs narrowed the candidate region to a 1,817 kb locus that extends from 10,425 to 12,266 kb in chromosome 12. Putative candidate genes that were identified by data mining and comparative sequence analysis can provide targets for further studies on mapping and cloning of the causal gene for PXO339 resistance in the MDILs. To our knowledge, this is the first report of a genetic locus from the allotetraploid wild rice, O. latifolia conferring race-specific resistance to bacterial blight.